Принципы раскрытия в толковом словаре стилистической маркированности фразеологических единиц (на материале немецкого языка) - Бердимуратов, Д.У.; Тажигалиева, М. (SCIENCE and SOCIETY, 2021)
The article discusses the semantic and stylistic marking of phraseological units, due to the constantly acting tendencies in phraseology to renew expressiveness. It is about the sequences of information disclosure.
Keywords: phraseological unit; phraseological nest; semantic and stylistic marking; semantic and stylistic interpretation; phraseological scheme; verbal component; phraseological form; lexical system; stylistic assessment; microgroup